Exploring the Role of SRC in Extraocular Muscle Fibrosis of the Graves’ Ophthalmopathy - Hao, Mingyu; Sun, Jingxue; Zhang, Yaguang; Zhang, Dexin; Han, Jun; Zhang, Jirong; Qiao, Hong (Frontiers in Bioengineering and Biotechnology, 2020)
The Graves' disease is an autoimmune disease highly associated with thyroid cancer, which extrathymic complication is an inflammatory ophthalmopathy called Graves' ophthalmopathy (GO). GO is caused by orbital fat formation and extraocular muscle fibrosis due to inflammation of the orbital connective tissue. Controlling extraocular muscle fibrosis is closely related to the prognosis of GO. In our study, we created a GO mouse model, which was subjected to transcriptome sequencing of the extraocular muscles of fibrotic GO mice, and the differentially expressed SRC genes of extraocular muscle fibrosis was found. Subsequently, we selected primary cultured orbital fibroblasts (OF) as a cell model for studying extraocular muscle fibrosis in vitro. Transforming Orbital fibroblasts into myofibroblasts (MFB) induced by TGF-β, which is transformation to express α-SMA. Myofibroblasts is an important target cell in the process of fibrosis. In our study, we performed SRC gene silencing on OF and found that SRC gene silencing inhibited the process of Transforming Orbital fibroblasts into myofibroblasts. In the next experiment, we inhibited TGF-β/Smad, NF-κB, and PI3K/Akt signaling pathways to analyze the interaction between the above signaling pathway and the SRC gene.